THU0424 Articular involvement in systemic sclerosis: comparison of clinical, radiographic and sonographic findings. (12th June 2018) - Thietart, S.; Louati, K.; Gaigneux, E.; Gatfosse, M.; Riviere, S.; Sellam, J.; Berenbaum, F.; Fain, O.; Mekinian, A.
Abstract : Background: Joint involvement in Systemic Sclerosis (SSc) is frequent and varied. 1, 2 Objectives: We study US synovitis and its correlation with clinical synovitis, radiological erosions and organ involvement. Methods: In a prospective cohort of SSc patients, tender and swollen joint counts, DAS28-CRP, hand US sonographies, X-ray hand views, as well as respiratory, cardiac, cutaneous and renal characteristics were assessed. Results: 54 patients were included with a median age of 59 years, 27–81 45 women (83%), with a diffuse cutaneous subtype in 13 patients (24%). 23 patients (52%) presented with arthralgia, 9 had clinical synovitis (16%) and DAS28-CRP of 3.7 (2.98–5.90). US sonography (34 patients) found at least one synovitis in 23 patients: 14 patients with grade 1 (66%), 6 patients grade 2 (29%), 1 patient grade 3 (5%), with a positive power Doppler signal in one case (3%). Among the patients having US-synovitis, 4 had clinical synovitis (17%), and 4 had X-ray erosions (17%). Radiological erosions were present in 8 patients (15%), without any correlation with clinical or US synovitis. Articular involvement (defined as clinical synovitis, US-synovitis and/or articular erosions) were found more frequently in limited SSc (n=28, 72%) than in diffuse SSc (n=4, 31%) (p<0.001), with a more frequent positivity of anti-centromere antibodies (n=23, 60% versus n=3, 20%). No correlation was found with disease severity or other organ impairment. Conclusions: US synovitis were found more frequently than clinical synovitis, which are merely active, and did not correlate with articular destruction. References: [1] Avouac J, Walker U, Tyndall A, Kahan A, Matucci-Cerinic M, Allanore Y, et al. Characteristics of joint involvement and relationships with systemic inflammation in systemic sclerosis: results from the EULAR Scleroderma Trial and Research Group (EUSTAR) database. J Rheumatol. 2010July;37(7):1488–501. [2] Elhai M, Guerini H, Bazeli R, Avouac J, Freire V, Drapé J-L, et al. Ultrasonographic hand features in systemic sclerosis and correlates with clinical, biologic, and radiographic findings. Arthritis Care Res (Hoboken). août2012;64(8):1244–9. Disclosure of Interest: None declared